Interactividad, visibilidad y contenido de medios digitales orenses - Alvarado Tigrero, Martha Guadalupe (Machala, 2019)
The following research work compiles information from various Orense Digital Media, which users prefer to be informed almost immediately of a news that has happened in the locality or the entire world, through the analysis of cases are determined the most positioned media, with more followers, and those that broadcast a greater number of content in the period of August 2019 through the Facebook Social Network. The Digital Media in the city of Machala are fundamental tools with a great boom in digital platforms, users access through a mobile device or Smartphone connected to the Internet to obtain different types of content that each page publishes daily through their social networks such as Facebook, Twitter, Instagram, YouTube and Web pages accompanied by images and videos. In addition, they have managed to migrate traditional media such as press, radio and television to digital platforms to be in contact with their followers and disseminate content from social networks. The objective of the research was to identify the most positioned digital media in the province of El Oro, their contribution as sources of employment for professionals in social communication, also determine the skills that should have a professional in social communication within the digital media according to the contribution of authors who have researched related to the skills and abilities of the social communicator. Case analysis was used using the methodology of Huertas, Setó and Miguez, to define the variables and indicators that would be measured in the research, in turn interviews were conducted with social communication professionals and owners of digital media orenses for obtaining data, computer applications were used to facilitate the interpretation of data and programs to measure the interaction of users of Digital Media. For the presentation of the results of the investigation, tables were used in which the answers obtained in the different interviews with professionals and owners of digital media were ordered. These were interpreted in chapter 4 of this work, evidenced by means of statistical graphs generated according to the information obtained from each Digital Media to make visible the percentage of the variables to be measured during the month of August and distributed in phases to show the conclusions and recommendations of the investigative work. The digital media with the highest positioning in the city of Machala was determined, according to the comparison of the number of followers and I like, obtained in the social network Facebook, the amount and type of content that was published in August, to measure the interaction that these digital media have. As a result of the investigation, El Machaleño Digital Media was determined to be the most positioned in the Orenses, having the greatest number of Followers and I Like within its page, being the one that shares the greatest number of varied content between news, advertising, sports, live transmissions, interviews and reports and the one that has the greatest interactivity with its followers.
El siguiente trabajo investigativo, compila información de varios Medios Digitales Orenses, que los usuarios prefieren para poder informarse de manera casi inmediata de una noticia que ha sucedido en la localidad o el mundo entero, mediante el análisis de casos se determinan los medios más posicionados, con mayor número de seguidores, y los que difunden un mayor número de contenido en el periodo del mes de agosto del 2019 a través de la Red social de Facebook. Los Medios Digitales en la ciudad de Machala son herramientas fundamentales con un gran auge en las plataformas digitales, los usuarios acceden mediante un dispositivo móvil o Smartphone conectado a internet para poder obtener diferentes tipos de contenidos que cada página publica diariamente a través de sus redes sociales como Facebook, Twitter, Instagram, YouTube y Páginas web acompañado de imágenes y videos. Además, han logrado que los medios tradicionales como prensa, radio y televisión migren a las plataformas digitales para estar en contacto con sus seguidores y difundan contenido desde las redes sociales. El objetivo de la investigación fue identificar al medio digital más posicionado de la provincia de El Oro, su aporte como fuentes generadoras de empleo para profesionales en comunicación social, además determinar las competencias que debe poseer un profesional en comunicación social dentro de los medios digitales de acuerdo al aporte de autores que han investigado relacionados con las competencias y habilidades del comunicador social. Se utilizó el análisis de casos mediante la metodología de Huertas, Setó y Miguez, para definir las variables e indicadores que serían medidos en la investigación, a su vez se realizaron entrevistas a profesionales en comunicación social y propietarios de medios digitales orenses para la obtención de datos, se emplearon aplicaciones informáticas para facilitar la interpretación de datos y programas para medir la interacción de usuarios de Medios Digitales. Para la presentación de los resultados de la investigación, se utilizaron tablas en las que se ordenaron las respuestas obtenidas en las diferentes entrevistas a profesionales y propietarios de medios digitales, las que se interpretaron en el capítulo 4 de este trabajo, se evidenciaron mediante gráficos estadísticos generados de acuerdo a la información obtenida de cada Medio Digital para visibilizar el porcentaje de las variables a medirse durante el mes de agosto y distribuidas en fases para mostrar las conclusiones y recomendaciones del trabajo investigativo. Se determinó el medio digital con mayor posicionamiento en la ciudad de Machala, de acuerdo a la comparación del número de seguidores y me gusta, obtenidos en la red social Facebook, la cantidad y el tipo de contenidos que se publicaron en el mes de agosto, para medir la interacción que tienen estos medios digitales. Como resultado de la investigación se determinó al Medio Digital El Machaleño como el más posicionado en los Orenses, teniendo un número mayor de Seguidores y Me Gusta dentro de su página, siendo el que comparte mayor número de contenido variado entre noticias, publicidad, deporte, transmisiones en vivo, entrevistas y reportajes y el que posee mayor interactividad con sus seguidores.
Keywords: MEDIO DIGITAL; EMPRENDIMIENTO; CIBERPERIODISMO; FACEBOOK